ASSESSING THE FINANCIAL FEASIBILITY OF MAGGOT FARMING: A CASE STUDY OF NYAMPIH - Intan Nurhaliza (Journal of Social and Economics Research, 2024)
The increasing amount of organic waste in Indonesia, which accounts for almost 50% of the total waste generated poses a significant challenge in waste management. This problem is worsened by the limitations of existing waste management models, particularly their real-world impact and economic benefits. The purpose of this study is to assess the financial feasibility of Black Soldier Fly (BSF) maggot farming as an innovative solution to Indonesia's organic waste problem. BSF maggots not only reduce organic waste but also generate economically valuable products such as animal feed and organic fertilizer. This study aims to assess the financial feasibility of a Black Soldier Fly (BSF) maggot farming project undertaken by Nyampih, a waste-management startup based in Sumedang, West Java. The study utilizes internal data from Nyampih's financial plan, company reports, and interviews, along with external data from government data, industry benchmarks, and relevant research. The analysis is limited to ten-year projections and focuses on financial feasibility. This study finds that the project is feasible and potentially profitable, with a net present value (NPV) of IDR 2,905,018,264.74, an internal rate of return (IRR) of 41.20%, a payback period of 3.88 years, a discounted payback period of 4.87 years, and profitability index of 5.77. However, the project has financial risks, particularly concerning the sales and price of maggot flour, which is projected to have the highest sales volume and price. Operating costs, COGS, and dried maggot sales and pricing also show sensitivity to NPV fluctuations. This emphasizes the importance of continuous monitoring and adjustment of marketing strategy, product proportions, pricing strategies, and cost structures to align with actual market conditions.